The hippocampus and exploration: dynamically evolving behavior and neural representations - Johnson, Adam; Varberg, Zachary; Benhardus, James; Maahs, Anthony; Schrater, Paul (Frontiers in Human Neuroscience, 2012)
We develop a normative statistical approach to exploratory behavior called information foraging. Information foraging highlights the specific processes that contribute to active, rather than passive, exploration and learning. We hypothesize that the hippocampus plays a critical role in active exploration through directed information foraging by supporting a set of processes that allow an individual to determine where to sample. By examining these processes, we show how information directed information foraging provides a formal theoretical explanation for the common hippocampal substrates of constructive memory, vicarious trial and error behavior, schema-based facilitation of memory performance, and memory consolidation.